2022
DOI: 10.1038/s41420-022-00894-w
|View full text |Cite
|
Sign up to set email alerts
|

Myoglobin promotes macrophage polarization to M1 type and pyroptosis via the RIG-I/Caspase1/GSDMD signaling pathway in CS-AKI

Abstract: Crush syndrome (CS) is a life-threatening illness in traffic accidents and earthquakes. Crush syndrome-induced acute kidney injury (CS-AKI) is considered to be mainly due to myoglobin (Mb) circulation and deposition after skeletal muscle ruptures and releases. Macrophages are the primary immune cells that fight foreign substances and play critical roles in regulating the body’s natural immune response. However, what effect does myoglobin have on macrophages and the mechanisms involved in the CS-AKI remain uncl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 106 publications
(58 reference statements)
0
28
0
Order By: Relevance
“…In the acute stage of influenza infection, macrophages are polarized into M1 phenotype and release abundant proinflammatory proteins and reactive oxygen species (ROS) [10]. Studies indicated that ROS released by M1 macrophages were prone to causing pyroptosis via activating the NLR family pyrin domain containing 3 (NLRP3) /gasdermin D (GSDMD) pathway [11][12][13]. Additionally, macrophage polarization may be regulated by Apolipoprotein E (ApoE) signaling [14], and the ApoE/LDLR pathway was suggested to be a potential signaling pathway involved in antiinflammation and antioxidation [15].…”
Section: Introductionmentioning
confidence: 99%
“…In the acute stage of influenza infection, macrophages are polarized into M1 phenotype and release abundant proinflammatory proteins and reactive oxygen species (ROS) [10]. Studies indicated that ROS released by M1 macrophages were prone to causing pyroptosis via activating the NLR family pyrin domain containing 3 (NLRP3) /gasdermin D (GSDMD) pathway [11][12][13]. Additionally, macrophage polarization may be regulated by Apolipoprotein E (ApoE) signaling [14], and the ApoE/LDLR pathway was suggested to be a potential signaling pathway involved in antiinflammation and antioxidation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research indicated that Mb causes RM-AKI through three mechanisms including Mb toxicity, iron dissociation and free radicals release, and lipid peroxidation [10]. So, the detection of Mb protein deposition is a key factor for the basic research of Mb-associated diseases, such as RM-AKI or CS-AKI [50]. In addition, Mb is the key earliest biomarker for ischemic heart disease [12,51] and the routine biochemical indicator for hospital testing of rhabdomyolysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, we summarized the therapeutic strategy of the CW formula from three aspects. To begin with, SR, GB, and DC have anti-inflammatory and anti-oxidant activities, all of which contribute to the resolution of inflammation and inflammation-compromised epithelial barrier function and pain ( Baskol et al, 2008 ), as evidenced by the markedly decreased IL-1b expression and CASP3-dependent pyroptosis ( Naji et al, 2016 ; Li et al, 2022 ) in murine colitis models subjected to the CW therapy. Mφs are a paradigm of immune cells with a highly plastic capacity able to change their phenotypes in response to environmental cues.…”
Section: Discussionmentioning
confidence: 99%